PERBEDAAN GANGGUAN MOBILITAS DITINJAU BERDASARKAN KARAKTERISTIK PASIEN PASCA STROKE DI POLI REHABILITASI MEDIK RSUD ULIN BANJARMASIN - Luthfiyyah, Rifaa; Siddik, Muhammad; Sanyoto, Didik Dwi; Hayati, Azka; Fakhrurrazy, Fakhrurrazy (Homeostasis, 2024)
Abstract: Stroke results in limited mobility. Mobility impairment due to stroke affects functional activities. The research aims to determine whether there are differences in mobility impairment in post-stroke patients based on patient characteristics. The method used is observational analysis with a cross-sectional design. The data used is primary data from examination observations using the Functional Ambulation Category questionnaire. This research targets the population of post-stroke patients at the Medical Rehabilitation Clinic. Number of samples in the period November-December 2023 using purposive sampling technique. The results of the study did not show a relationship between mobility impairment in terms of gender, age, stroke onset, lesion location, Brunstrom stage, history of attacks, comorbidities and history of therapy in post-stroke patients. From the results of the study, no relationship was found between mobility impairments based on the characteristics of post-stroke patients in the medical rehabilitation clinic at Ulin District Hospital, Banjarmasin. Keywords: Mobility disorders, post-stroke patients, Functional Ambulation Category Abstrak: Stroke mengakibatkan keterbatasan mobilitas. Gangguan mobilitas akibat stroke mempengaruhi aktivitas fungsional. Penelitian bertujuan mengetahui apakah terdapat perbedaan gangguan mobilitas pada pasien pasca stroke yang ditinjau berdasarkan karakteristik pasien. Metode yang digunakan adalah analisis observasional dengan desain potong lintang. Data yang digunakan adalah data primer pengamatan pemeriksaan menggunakan kuesioner Functional Ambulation Category. Penelitian ini menargetkan populasi pasien post stroke Poli Rehabilitasi Medik. Jumlah sampel pada periode November-Desember 2023 dengan teknik purposive sampling.  Hasil penelitian tidak di dapatkan hubungan antara gangguan mobilitas ditinjau dengan jenis kelamin,usia,onset stroke,letak lesi,stadium brunnstrom,riwayat serangan,komorbid dan riwayat terapi pada pasien pasca stroke. Dari hasil penelitian tidak didapatkan hubungan antara gangguan mobilitas ditinjau berdasarkan karakteristik pasien pasca stroke di poli rehabilitasi medik RSUD Ulin Banjarmasin. Kata-kata kunci: Gangguan mobilitas, pasien pasca stroke, Functional Ambulation Category.